EtCO2-Based Biofeedback Method of Breath Regulation Increases Speech Fluency of Stuttering People - STANKIEWICZ, Barbara; ZIELIŃSKI, Krzysztof; DAROWSKI, Marek; MICHNIKOWSKI, Marcin (Archives of Acoustics, 2015)
Respiratory disturbances frequently accompany stuttering. Their influence on lung ventilation can be assessed by measurement of the end-tidal CO2 concentration (EtCO2). The effectiveness of the CO2-based visual feedback method of breath regulation (VF) designed for stuttering therapy was tested in this study. The aim of the study was to answer the question if the VF helps to reduce respiratory disturbances in stuttering and increase speech fluency. 20 stuttering volunteers aged 13–45 years took part in the 3-parts test consisting of: 1. speaking without any techniques improving speech fluency, 2. learning the VF method, 3. VF-assisted speaking. The CO2/time signal and an acoustic signal of an utterance were recorded during the test. Significant increase of FE – the factor of breath ergonomics during speaking (based on both signals), from 47% to 71% (P < 0.01), and significant decrease of %SS – the percent of syllables stuttered, from 14% to 10% (P < 0.01) were received for VF-assisted utterances compared to the utterances without VF assistance. The results indicate that the VF can help to eliminate respiratory disturbances in stuttering and increase speech fluency.